Performance of red seaweed for azo dye removal : acid yellow 17 - Farah Aqilah, Mustafa (2017)
In the treated effluents of industries, dyes are usually present in trace quantities. The untreated wastewaters containing dyes are aesthetically unpleasant and toxic which will greatly affect and pose environmental problems. The effluents commonly contain an amount of pollutants and contaminants. In order to remove these dyes, there are three methods available, which consists of biological method, chemical method and physical method. One of the physical method, adsorption is among the most effective techniques for dye removal from wastewater. Adsorption is an efficient way to remove synthetic dyes from industrial effluent. Therefore, this study was carried out to show mechanism of adsorptive removal of cationic dye acid yellow 17 (AY17) from its aqueous solution using dried biomass of seaweed Euchema Spinosum as a biosorbent. This study aims to determine the percentage of dye removal by seaweed and the optimum condition of dye removal in four parameters, which includes contact time, pH, biosorbent dosage and initial concentration. The results showed that the biomass exhibited the highest dye uptake capacity at initial pH value of 7, biosorbent dosage of 0.04g, contact time of 60 minutes and initial concentration of 100 mg/L. The adsorption results in this study indicated that the adsorbents were attractive candidates for removing acidic dyes from dye wastewater.